Consumo Voluntario de Forraje por Rumiantes en Pastoreo - Mejía Haro, José (Acta Universitaria, 2002)
The variation in voluntary forage intake is undoubtedly the major dietary factor determining level and efficiency of ruminant production. This variation is bigger and least predictable for grazing ruminants. Range ruminant productivity and efficiency is relatively low due, partly, to intake limitations; productivity could probably be increased most by increasing intake. Distension of the reticulo-rumen wall is the primary intake regulation mechanism of low-quality roughages in range ruminants, digestibility and rate of ingest passage also affect voluntary intake. Body size and metabolic bodysize as well affect intake of grazing animals. Kind and amount of supplementation, forage availability, and grazing intensity have been related to voluntary forage intake.